2016
DOI: 10.1212/wnl.0000000000002329
|View full text |Cite
|
Sign up to set email alerts
|

Fitness and cognition in the elderly

Abstract: Objective: To investigate whether greater cardiorespiratory fitness is associated with better global and domain-specific cognitive function. Methods:We investigated 877 participants (aged 65 6 7 years, 55% women) of the Austrian Stroke Prevention Study. For cardiorespiratory fitness, the maximum oxygen consumption (VȮ 2 max) was calculated based on weight and maximum and resting heart rate on a treadmill test (mL$kg 21 $min 21 ). A test battery assessing memory (Bäumler's Lern-und Gedächtnistest), executive fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(24 citation statements)
references
References 40 publications
1
22
0
1
Order By: Relevance
“…The measures of the cognitive performance were converted into z-scores by normalizing to the mean of the group. G-factor, which is the first unrotated component of 1 SIENEX, part of FMRIB Software Library; https://fsl.fmrib.ox.ac.uk/fsl/fslwiki/ principal component analysis performed on the results of the battery of cognitive tests, was used as a measure of global cognition (17).…”
Section: Cognitive Testingmentioning
confidence: 99%
“…The measures of the cognitive performance were converted into z-scores by normalizing to the mean of the group. G-factor, which is the first unrotated component of 1 SIENEX, part of FMRIB Software Library; https://fsl.fmrib.ox.ac.uk/fsl/fslwiki/ principal component analysis performed on the results of the battery of cognitive tests, was used as a measure of global cognition (17).…”
Section: Cognitive Testingmentioning
confidence: 99%
“…Likewise, two studies noticed a superior improvement in aerobic capacity in older adults who underwent ST. (Brentano et al, 2008;Vincent et al, 2002) A higher cardiac output, characterized by an augmentation in blood flow, associated with increased capitalization and improvements in respiratory chain function, are considered possible mechanisms by which AE training leads to improvement in VO2max. (Freudenberger et al, 2016) , (Bassett & Howley, 2000) Also, several physiological adaptations to ST may be accounted for improvements in aerobic capacity in older adults, such as augmentation of capillary density, myoglobin concentration, mitochondria content and enzyme activity in the working muscle. (Brentano et al, 2008;Cadore et al, 2010;Ozaki et al, 2013;Phillips et al, 2012) These physiological adaptations may lead to increase in arterial-venous oxygen difference (a-vO2), which associated with elevated exercise-induced blood flow, are the key-factors that of STinduced improvements in VO2max.…”
Section: Improvements In Vo2maxmentioning
confidence: 99%
“…Huang et al, 2015;Lakka et al, 2003;Vanhees, De Sutter, et al, 2012;Vanhees, Rauch, et al, 2012) and it is inversely associated with healthy cognitive functioning. (Freudenberger et al, 2016) In the past decades, several studies have reported a positive relationship between high physical activity levels and improved arterial compliance (i.e., increased arterial elasticity). (Cameron & Dart, 1994;Cameron, Rajkumar, Kingwell, Jennings, & Dart, 1999;Otsuki et al, 2006;Tanaka et al, 2000Tanaka et al, , 1998 Regular aerobic-based exercise is a nonpharmacological strategy that seems to attenuate and partially reverse age-induced arterial stiffening by increasing arterial compliance (Cameron & Dart, 1994;Lu, Hui-Chan, & Tsang, 2013a, 2013bMaeda et al, 2008;Miyaki et al, 2009;Nickel, Acree, & Gardner, 2011;Parnell, Holst, & Kaye, 2002;Seals, Desouza, Donato, & Tanaka, 2008;Sugawara et al, 2009;Sugawara, Inoue, Hayashi, Yokoi, & Kono, 2004;Tanaka et al, 2000;Vanhees, Rauch, et al, 2012;Villareal, Smith, Sinacore, Shah, & Mittendorfer, 2011) and VO2max,(G. Huang et al, 2015;Vanhees, De Sutter, et al, 2012;Vanhees, Rauch, et al, 2012) thereby, leading to improved health outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…In older adults, CRF has been reported to be positively associated episodic memory (Etnier et al., 2007; Hayes, Forman, & Verfaellie, 2016; Zhu et al., 2014), while others have not observed such associations in similar populations (Bugg et al., 2012; Maass et al., 2015). Moreover, both self‐reported physical activity (Pizzie et al., 2014) and estimated fitness (Boots et al., 2014; Freudenberger et al., 2016) have been shown to be positively associated with episodic memory in older adulthood.…”
Section: Introductionmentioning
confidence: 99%